Prognostic factors for ESD of early gastric cancers: a systematic review and meta-analysis - De Marco, Michele Oliveira; Tustumi, Francisco; Brunaldi, Vitor Ottoboni; Resende, Ricardo Hannum; Matsubayashi, Carolina Ogawa; Baba, Elisa Ryoka; Chaves, Dalton Marques; Bernardo, Wanderley Marques; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2020)
Background and study aims Gastric neoplasms are one of the leading types of cancer in the world and early detection is essential to improve prognosis. Endoscopy is the gold-standard diagnostic procedure and allows adequate treatment in selected cases. Endoscopic submucosal dissection (ESD) has been reported to safely address most early gastric cancers (EGCs), with high curability rates. However, data on prognostic factors related to ESDs of EGCs are conflicting. Therefore, we aimed to systematically review the available literature and to perform a meta-analysis to identify the relevant prognostic factors in this context.Methods We performed this study according to PRISMA guidelines. Comparative studies assessing the relationship between curative resection or long-term curability rates and relevant prognostic factors were selected. Prognostic factors were demographic data, lesion features (location, morphology of the lesion, size, and depth of invasion), histological findings, Helycobacter pylori (HP) infection, presence of gastric a atrophy and body mass index (BMI). Finally, we also evaluated risk factors related to metachronous gastric neoplasm.Results The initial search retrieved 2829 records among which 46 studies were included for systematic review and meta-analysis. The total sample comprised 28366 patients and 29282 lesions. Regarding curative resection, pooled data showed no significant influence of sex [odds ratio (OR): 1.15 (0,97, 1.36) P = 0.10 I2 = 47 %] , age [OR: 1.00 (0.61, 1.64) P = 1.00 I2 = 58 %], posterior vs non-posterior location [OR: 1.35 (0.81, 2.27) P = 0.25 I2 = 84 %], depressed vs von-depressed macroscopic type[OR: 1.21 (0.99, 1.49) P = 0.07 I2 = 0 %], non-upper vs upper location [OR: 1.41 (0.93, 2.14) P = 0.10 I2 = 77 %] and BMI [OR: 0.84 (0.57; 1.26) P = 0.41 I2 = 0 %]. Differentiated neoplasms presented greater chance of cure compare to undifferentiated [OR: 0.10 (0.07, 0.15) P < 0.00001 I2 = 0 %]. Ulcerated lesions had lower curative rates compared to non-ulcerated [OR: 3.92 (2.81, 5.47) P < 0.00001 I2 = 44 %]. Lesions smaller than 20 mm had greater chance of curative resection [OR: 3.94 (3.25, 4.78) P < 0.00001 I2 = 38 %]. Bleeding during procedure had lower curative rates compared to non-bleeding [OR: 2.13 (1.56, 2.93) P < 0.0001 I2 = 0 %]. Concerning long-term cure, female gender [OR 1.62 (1.33, 1.97) P < 0.00001 I2 = 0 %] and the mucosal over SM1 cancers were protective factors [OR: 0.08 (0.02, 0.39) P = 0.002 I2 = 86 %]. Gastric atrophy [OR: 0.60 (0.45, 0.81) P = 0.0006 I2 = 42 %] and the pepsinogen I/pepsinogen II ratio [OR 2.29 (1.47, 3.57) P = 0.0002 I2 = 0 %] were risk factors to metachronous gastric neoplasm.Conclusions Ulcerated lesions, histology, bleeding and size > 20 mm are prognostic factors concerning curative resection. Regarding long-term cure, female gender and mucosal over SM1 cancer are predictive factors. Gastric atrophy and the pepsinogen ratio are risk factors for metachronous gastric neoplasm.